Análise comparativa das propriedades reológicas e mecânicas de três argamassas autonivelantes comerciais - Casali, Juliana Machado; Nunes, Lucas Elia; Silveira, Luis Gustavo; Rosa, Alice Cordeiro da; Reichmann, Amanda da Maia; Calçada, Luciana Maltez (Ambiente Construído, 2026)
The objective of this study was to compare three commercially available industrialized self-leveling mortars. The mortars were mixed using a rheometer in order to observe their mixing efficiency. In fresh state fluidity, spreading, rheological parameters (oscillatory tests and rotational flow cycles) and regeneration time were evaluated. In the hardened state, flexural tensile strength, compressive strength and dynamic modulus of elasticity were evaluated. The results showed variations in mixing efficiency, and the mortars present yield stress near to zero. These variations indicate that each formulation has unique characteristics, even though they were developed for the same purpose.